Epidemiological Characteristics Of Neonatal Mortality In The National Perinatal Maternal Institute INMP 2015 - 2016 - Dávila-Aliaga, Carmen Rosa (2019)
Objective: To determine the causes of neonatal mortality and its epidemiological characteristics in our institution, 2015and 2016. Materials and methods: Retrospective, descriptive and observational study, we reviewed the clinical records ofpatients who died in the neonatal department of the INMP during 2015 and 2016.